Legend - Lu, Marie (New York : Scholastic, 2011)
In a dark future, when North America has split into two warring nations, fifteen-year-olds Day, a famous criminal, and prodigy June, the brilliant soldier hired to capture him, discover that they have a common enemy.
M
710
M